Bagaimana Kualitas Pelayanan Mempengaruhi Kepuasan Pelanggan di Starbucks Coffee di Ambarrukmo Plaza, Yogyakarta - , FINDRIANE FEBRILLA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The background of this research aims to elaborate the company profile of Starbucks Coffee Company and its store in Ambarrukmo Plaza and to analyze the customer satisfaction in Starbucks Coffee store at Ambarrukmo Plaza. Besides, Starbucks Ambarrukmo Plaza is the only one Starbucks Coffee store which located in Yogyakarta. The writer used SERVQUAL dimensions which proposed by Parasuramanet. al.,(1988). There are five dimensions used in this research, such as: reliability, assurance, tangible, empathy, and responsiveness. The writer used field study and library study method. The field study methods were done by conducting direct observation and distributing questionnaire. The library study method was conducted by reading the theories proposed by Parasuramanet. al. From the result of study using SERVQUAL dimension, it is found that those five dimensions affect customer satisfaction in Starbucks store Ambarrukmo Plaza. Friendliness and respect aspect asE2 and E3 in empathy dimension give dominant effect to customer satisfaction in Starbucks Coffee Ambarrukmo Plaza with its 86.9% of satisfy value.Moreover, technology aspect in tangible dimension as T3 gives the highest value of dissatisfied from those five dimensions with its 29% value. The writer got the research data by distributing questionnaire in hectic hour and quiet hour in Starbucks Ambarrukmo Plaza. In conclusion, the result of this research finds that customer satisfaction could be achieved when good performance from the employee meets the expectation of the customer towards the service.